The labyrinth of time : introducing the universe - Lockwood, Michael (Michael John) (OUP E-Books., 2005)
Modern physics has revealed the universe as a much stranger place than we could have imagined. The puzzle at the centre of our knowledge of the universe is time. Michael Lockwood takes the reader on a fascinating journey into the nature of things. He investigates philosophical questions about past, present, and future, our experience of time, and the possibility of time travel. And he provides the most careful, lively, and up-to-date introduction to the physics of time and the. structure of the universe. His aim is not just to boggle the mind, but to lead the reader towards an understanding of.